2019
DOI: 10.20473/fmi.v55i1.12559
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Lower Limb Muscles and Body Mass Index with Body Balance in the Elderly

Abstract: Indonesia enters the ageing population because of increasing elderly population. The large number of ederly population can have negative impact if they have some problems, such as increased disability and increased rates of life dependence. Based on health research, it was mentioned that the cause of the most injuries to the elderly group is falls that are caused by balance disorder. Balance problems can be caused by changes of musculoskeletal function. In addition, Body Mass Index (BMI) is still a problem tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“… 2 , 3 ) The lower limb muscle strength is strongly positively correlated with body balance in older adults. 17 ) Strength and balance are often significant contributors to mobility limitations, and aerobic capacity, often measured as maximal oxygen uptake (VO 2max ) or peak oxygen uptake (VO 2peak ), also correlates with self-reported difficulty and disability and timed functional performance in older adults. 18 )…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 ) The lower limb muscle strength is strongly positively correlated with body balance in older adults. 17 ) Strength and balance are often significant contributors to mobility limitations, and aerobic capacity, often measured as maximal oxygen uptake (VO 2max ) or peak oxygen uptake (VO 2peak ), also correlates with self-reported difficulty and disability and timed functional performance in older adults. 18 )…”
Section: Discussionmentioning
confidence: 99%
“…From the researcher's point of view, the reason behind the emergence of the highest percentage of participants in the category of moderate and high risk of falling are that the participants in the study suffer from more than one disease, use of more than one medication and the lack of regular exercise by the participants in the study, all these factors make a person vulnerable to falling at a moderate to high rate. Valentina et al, (2019) they found in a study conducted in Indonesia that (20.5%) had a high risk for falls, (35.9%) had a moderate risk for falls and (43.6%) had a low risk for fall (. Valentina et al, 2019).…”
Section: Table (1)mentioning
confidence: 99%
“…Valentina et al, (2019) they found in a study conducted in Indonesia that (20.5%) had a high risk for falls, (35.9%) had a moderate risk for falls and (43.6%) had a low risk for fall (. Valentina et al, 2019).…”
Section: Table (1)mentioning
confidence: 99%
“…12 As a correction for the ageing process, the numbers acquired from the leg dynamometer are increased by 10% in the elderly. 13 The Time Up and Go Test (TUGT) is a simple test that aims to assess functional status such as mobility, balance, walking ability, and the risk of falls in the elderly. 14 The time measurement instrument uses a Seiko brand stopwatch with an accuracy of 0.01 seconds.…”
Section: Research Instrumentmentioning
confidence: 99%